1973
DOI: 10.1111/j.1365-3083.1973.tb02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fibril Protein Subunit,‘Protein AS’: Distribution in Tissue and Serum in Different Clinical Types of Amyloidosis Including that Associated with Myelomatosis and Waldenström's Macroglobulinaemia

Abstract: Gel filtration of degraded amyloid fibrils, derived from patients with different clinical types of amyloidosis, revealed a nonimmunoglobulin protein of low molecular weight (protein AS). This protein was previously found in amyloidosis secondary to chronic inflammation. In this study it was also shown to be present in amyloid connected with certain cases of primary amyloidosis and amyloidosis associated with myelomatosis and Waldenström's macroglobulineamia with Bence‐Jones proteinuria. Furthermore, a serum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…DISCUSSION The nonimmunoglobulin amyloid protein AS with the reported molecular weight of 7,000-9,000 daltons (10,19,20) corresponding to 76 amino acids (20) is shown to be an integral part of the amyloid substance in secondary amyloidosis (8,10,19). In addition, we have recently demonstrated the presence of protein AS in amyloid preparations derived from patients with primary amyloidosis as well as amyloidosis associated with myelomatosis or macroglobulinemia (9,12). It has been shown that protein AS can form fibrils (8,21,22).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…DISCUSSION The nonimmunoglobulin amyloid protein AS with the reported molecular weight of 7,000-9,000 daltons (10,19,20) corresponding to 76 amino acids (20) is shown to be an integral part of the amyloid substance in secondary amyloidosis (8,10,19). In addition, we have recently demonstrated the presence of protein AS in amyloid preparations derived from patients with primary amyloidosis as well as amyloidosis associated with myelomatosis or macroglobulinemia (9,12). It has been shown that protein AS can form fibrils (8,21,22).…”
Section: Resultsmentioning
confidence: 98%
“…The molecular weight of protein ASC (100,000) is far higher than that of protein AS (9,145) as determined by the total amino acid sequence (20). Levin et al (10) suggested that protein AS is a fragment of a larger protein, since the N-terminal part of the protein in their experiments seemed to be heterogenous.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown to have 76 amino acid residues in a single chain with a molecular weight of 8500 daltons although minor substitutions have been reported (2). Although this protein was the major constituent of amyloid fibrils isolated from a patient with familial Mediterranean fever (FMF) (2), other investigators have found a smaller percentage in amyloidotic tissues (5,6).…”
Section: Isolation O F a Cross-reacting Component From Serum By Affinmentioning
confidence: 99%